2008
DOI: 10.1136/jech.2008.077602
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and fasting glucose in a developing southern Chinese population: the Guangzhou Biobank Cohort Study

Abstract: In an understudied population with a different pattern of alcohol use from the populations usually studied, the biologically expected effects of moderate alcohol use were seen, but there was little effect on fasting glucose. Although cross-sectional studies cannot be conclusive, this pattern of findings, if confirmed, suggests that moderate alcohol use may not affect fasting glucose, although excessive use may be a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Recently, the views about protective effects of moderate alcohol consumption on healthy consequence have also been questioned. Several cohort studies have demonstrated that moderate alcohol use is not beneficial for heart function via QT interval or heart rate in men[21], but associated with higher fasting glucose[22]as well as increased alcohol related cancers in women[23]. In our study, long-term drinking (≥ 35 years)even with alleged moderate rang (80–210 g/week), was still a risk factor for NAFLD in elder men (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the views about protective effects of moderate alcohol consumption on healthy consequence have also been questioned. Several cohort studies have demonstrated that moderate alcohol use is not beneficial for heart function via QT interval or heart rate in men[21], but associated with higher fasting glucose[22]as well as increased alcohol related cancers in women[23]. In our study, long-term drinking (≥ 35 years)even with alleged moderate rang (80–210 g/week), was still a risk factor for NAFLD in elder men (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…First, alcohol use was self-reported, but we have previously validated self-reported alcohol use against HDL-cholesterol and ALDH2 polymorphisms 15 28. Second, this cohort may not be representative of all Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…In the neighbouring city of Hong Kong where the population shares a common ancestry with the participants in GBCS, alcohol use less than or equal to 2 units/day for women and 3 units/day for men, where one unit is 10 g ethanol, has been considered as moderate 14. Therefore, this definition was used in this analysis, and was consistent with other papers using the same sample 15 16. Moderate alcohol users were defined as people using alcohol weekly with average consumption ≤140 g ethanol per week for women and ≤210 g for men.…”
Section: Methodsmentioning
confidence: 97%
“…Moreover, it is uncertain whether and to what extent that genetic backgrounds as well as lifestyle factors influence the association between alcohol intake and metabolic outcomes among difference ethical populations. So far, most of studies have been conducted among western populations and only one study investigated the relationship between alcohol intake and fasting glucose in Guangzhou, a southern city of China [6]. Given the substantial variations in lifestyles and disease patterns among peoples living in different geographic locations in China, more studies based on a representative sample of Chinese people are definitely warranted.…”
Section: Introductionmentioning
confidence: 99%